(untitled) (Research, Society and Development, 2021)
Forensic Dentistry uses dental mineralization to estimate age, in order to assist the estimation of cadavers and also living humans. The purpose of the study was to evaluate the reliability of the method proposed by Cornélio Neto (2000) to estimate human chronological age by analyzing third molars mineralization. The study used 150 panoramic x-rays of people from both sexes, on the age between 15 and 22 years and who had at least one of the third molars. According to the classification in Nicodemo, Moraes and Médici Filho (1974) and adapted by Cornélio Neto (2000), the mineralization stages of each element present on the radiography were recorded by a previously calibrated examiner. After the mineralization stages were stated, they were intented in the formulas developed by Cornélio Neto (2000) to estimate age, which varies according to each of the third molars and the sex of the owners. For data analysis, the Intraclass Correlation Coefficient test was performed, using the SPSS software (Version 27, Chicago, USA). In males, the tooth with the highest agreement rate was the eighteen, whereas in females, teeth were thirty-eight and forty-eight. The classification of agreement, proposed by Fermanian (1984), points out that the assessed third molars had a moderate correlation between real and estimated ages. Therefore, this method can be used as a complementary exam to estimate an individual’s real age, requiring other studies to corroborate his estimate.